Rural Libraries in Karnataka - Biradar, B. S. (Journal of Information and Knowledge, 1999)
Discribe the library situation in some of the rural parts of Karnataka. The collection, services, staff, building and furniture scenario in some of the libraries is given. The article suggests remedies for improvement.